The novel platinum(IV) complex LA-12 induces p53 and p53/47 responses that differ from the related drug, cisplatin - Hrstka, Roman; Powell, Darren J; Kvardova, Veronika; Roubalova, Eva; Bourougaa, Karima; Candeias, Marco M; Sova, Petr; Zak, Frantisek; Fåhraeus, Robin; Vojtĕsek, Borivoj (Anti-cancer drugs, 2008)
The platinum(II)-based complex cisplatin is one of the most frequently used antitumour agents; however, a high incidence of harmful side effects and the frequent emergence of acquired resistance are the major clinical problems. The novel platinum(IV)-based complex LA-12 exhibits a high efficacy against cancer cell lines, including cisplatin-insensitive cells, but the mechanisms by which LA-12 perturbs cell growth are unclear. We tested the effects of LA-12 on the p53 response and demonstrate that LA-12 induces unique changes in the profile of gene expression compared with cisplatin and doxorubicin. Furthermore, the ability of LA-12 to disrupt cellular proliferation is greatly enhanced by the expression of p53 and p53/47 indicating both p53-dependent and p53-independent effects of LA-12. Exposure of the human cancer cell lines H1299, A2780, BT549 and BT474 to LA-12 alters the expression of p53 and p53/47 in both a time-dependent and dose-dependent manner. Treatment of cells with a low concentration of the drug results in accumulation of p53 and p53/47 concomitant with their posttranslational modification, whereas a high dose results in the disappearance of both the forms of p53. The distinct p53 activation profile of LA-12 compared with cisplatin and doxorubicin provides a molecular explanation for the ability of this drug to treat cisplatin-resistant cells and indicates its potential usefulness as an alternative antitumour agent in first-line therapy or as a second-line therapy in patients with acquired cisplatin resistance.
Keywords: doxorubicin; Protein Isoforms; protinádorové látky; Cell Line, Tumor; Cell Proliferation; posttranslační úpravy proteinů; signální transdukce; vztah mezi dávkou a účinkem léčiva; chemorezistence; Amantadine; Organoplatinum Compounds; nádorový supresorový protein p53; Protein Processing, Post-Translational; protein - isoformy; amantadin; Flow Cytometry; Oligonucleotide Array Sequence Analysis; Signal Transduction; průtoková cytometrie; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; lidé; Humans; Cell Cycle; proliferace buněk; cisplatina; Drug Resistance, Neoplasm; buněčný cyklus; nádorové buněčné linie; organoplatinové sloučeniny; Cisplatin; Dose-Response Relationship, Drug; Doxorubicin; Tumor Suppressor Protein p53; Antineoplastic Agents